What does sounding Singaporean mean? - Tan, Charmaine Li Min (Nanyang Technological University, 2020)
As Singapore moves into the era of Artificial Intelligence, there is growing awareness of a need for local speech recognition. Earlier literature has illustrated spoken Singapore English features through comparisons with British English or American English. However, the field lacks a timely consolidation on which features are still present, have been abandoned, or shifted in Standard Singapore English (SSE) today. What does sounding Singaporean mean? This paper aims to investigate which vocalic features mark Singaporean speech, and if the phonetic patterns follow demographic trends of education levels and ethnicity. Using read sentences from the National Speech Corpus, monophthongs and diphthongs of interest were analysed by plotting out their vowel spaces and calculating the retention rates respectively. Results showed that neutralisation had occurred in all four long-short monophthong pairs, although the extent differs across pairs. All three diphthongs were reduced to monophthongs, and the realization of target words tomato and can’t showed varying influences of Americanisation. Comparative analysis revealed that intra-variation exists in SSE: secondary-educated speakers were more susceptible to shifts, while ethnic variation was more randomized. While there is no single prototype for sounding Singaporean, it is clear that our local accent differs from other Englishes from the segmental level.